Bridging the Gap in Learning Evaluation: A Mixed Methods Approach to Enhancing Educational Outcomes - Muhamad Wijaksono; Fitri Hilmiyati; Aas Siti Sholichah (Journal of Educational Management Research, 2025)
This paper emphasizes the urgency of implementing mixed methods in learning evaluation by integrating quantitative and qualitative data. This approach was chosen because learning evaluation cannot be understood solely through numbers or narrative descriptions; a synthesis of both types of data is necessary to obtain a complete picture of the learning process's effectiveness. This research employed a literature review method, analyzing evaluation theories, integration models, and the thinking of modern experts. The results of the study indicate that mixed methods can improve the accuracy, depth of analysis, and validity of findings through evidence triangulation. Furthermore, this approach allows evaluators to capture contextual aspects, such as motivation, interaction, and classroom dynamics, that may not be readily apparent in quantitative instruments. The integration of mixed methods also strengthens the basis for decision-making for educators and policymakers, enabling learning improvement processes to be more targeted and based on robust data. The research highlights the practical implications of adopting mixed methods in learning evaluation, emphasizing how this approach enhances the comprehensiveness of educational assessments. It provides educators and policymakers with a more nuanced understanding of learning dynamics, leading to more informed, context-sensitive decisions that drive practical educational improvements.